A methods engineering study on Marivel's Pillows - Agbay, Michael; Cuaresma, Aaron; Gayagoy, Bryan; Lauron, Jahnell (Diliman, Quezon City College of Engineering, 2003)
Marivel's Pillow is a small scale business that produces various sorts of pillow and comforter, which are then distributed to different provinces in Luzon. Their manufacturing plant consists of a production area and a separated warehouse. Methods engineering study was conducted on Marivel's Pillow to determine the different production problems of the company, and thus to allocate appropriate solutions to the problems found. With the use of a Stream Diagnostic Chart, three (3) main problems were found: Inefficient Plant Layout, Poor Organization of Materials and Insufficient Working Space. Inefficient Plant Layout is mainly due to the fact that the different divisions that compose the production plant of Marivel's Pillow are inappropriate. Poor Organization of Materials on the other hand, is due to the improper placement of the different materials and equipment used. Lastly, Insufficient Working Space is a consequence of the two problems mentioned above. Through the various solving problem techniques learned in IE 32, the researchers were able to come up with solutions to the three problems. For the Inefficient Plant Layout, two (2) proposed layout were made. Each layout has its own advantages. Although not yet tested, the 2 layout was designed to minimize production time and aid in an easier job for the workers. For the Organization of Materials, the different alternatives can be of great addition to the company : boxes for the closed, unclosed pillow, bonel and Polyester fiber. This would also be of great advantage. But more importantly, the problem of orderliness can be solved by just simply placing all the tools, materials and equipments used in its proper place. Lastly, the problem with Insufficient Working Space can be readily solved if the two problems above will be addressed properly. The researchers found out that the size of the plant is not actually insufficient it is just that the plant layout is not well designed and the messy atmosphere in the production and warehouse constitute this lack in spacing. With a proper layout and a well orderly plant, the problem with insufficient working space is easily solved.
Feasibility study
Keywords: Systems analysis